2007
DOI: 10.1161/atvbaha.106.137091
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Soluble Form of LR11, Specifically Expressed in Intimal Smooth Muscle Cells, Accelerates Formation of Lipid-Laden Macrophages

Abstract: Objective-Macrophages play a key role in lipid-rich unstable plaque formation and interact with intimal smooth muscle cells (SMCs) in early and progressive stages of atherosclerosis. LR11 (also called sorLA), a member of low-density lipoprotein receptor family, is highly and specifically expressed in intimal SMCs, and causes urokinase-type plasminogen activator receptor-mediated degradation of extracellular matrices. Here we investigated whether the secreted soluble form of LR11 (solLR11) enhances adhesion, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…For example, it has been shown that SorLA interacts with the amyloid precurcursor protein (38), a protein that is directly associated with development of Alzheimer's disease. SorLA might play a role in the regulation of formation of lipidladen macrophages in atherosclerotic plaques (39). Sortilin is involved in neuronal apoptosis through its interactions with proneurotrophins and p75 NTR (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that SorLA interacts with the amyloid precurcursor protein (38), a protein that is directly associated with development of Alzheimer's disease. SorLA might play a role in the regulation of formation of lipidladen macrophages in atherosclerotic plaques (39). Sortilin is involved in neuronal apoptosis through its interactions with proneurotrophins and p75 NTR (40).…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies against uPAR and HIF-1␣ were from R&D Systems and Cell Signaling Technology, respectively. Recombinant LR11 protein lacking the 104 C-terminal amino acids containing the transmembrane region (sLR11) was prepared as described (22).…”
Section: Methodsmentioning
confidence: 99%
“…The mouse stromal cells, OP-9, were provided by Dr. Osawa (Chiba University). For murine cell sorting, BM cells were first stained with biotinylated-anti-Lineage (Lin) (CD5, B220, CD11b, Gr-1, 7-4, Ter-119) followed by incubating with streptavidin microbeads (Miltenyi Biotec Cell Adhesion Assay-Cell adhesion was determined in 96-well plates as described (22). For experiments using vitronectin-coated plates, wells were coated with 10 ng/well vitronectin for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The protein concentrations were determined using the BCA Protein Assay Reagent (Pierce, Rockford, IL, USA). For immunoblotting, equal amounts of membrane protein, protein extracted from pelleted beads, or concentrated media were separated by 10% SDS-PAGE after heating to 95 1C for 5 min under reducing conditions, and transferred to a nitrocellulose membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%